Size‐dependent mortality of corals during marine heatwave erodes recovery capacity of a coral reef. (15th December 2021) - Speare, Kelly E.; Adam, Thomas C.; Winslow, Erin M.; Lenihan, Hunter S.; Burkepile, Deron E.
Abstract: For many long‐lived taxa, such as trees and corals, older, and larger individuals often have the lowest mortality and highest fecundity. However, climate change‐driven disturbances such as droughts and heatwaves may fundamentally alter typical size‐dependent patterns of mortality and reproduction in these important foundation taxa. Working in Moorea, French Polynesia, we investigated how a marine heatwave in 2019, one of the most intense marine heatwaves at our sites over the past 30 years, drove patterns of coral bleaching and mortality. The marine heatwave drove island‐wide mass coral bleaching that killed up to 76% and 65% of the largest individuals of the two dominant coral genera, Pocillopora and Acropora, respectively. Colonies of Pocillopora and Acropora ≥30 cm diameter were ~3.5× and ~1.3×, respectively, more likely to die than colonies <30‐cm diameter. Typically, annual mortality in these corals is concentrated on the smallest size classes. Yet, this heatwave dramatically reshaped this pattern, with heat stress disproportionately killing larger coral colonies and equalizing annual mortality rates across the size spectrum. This shift in the size‐mortality relationship reduced the overall fecundity of these genera by >60% because big corals are disproportionately important for reproduction on reefs. Additionally, the survivorship of microscopic coral recruits, critical for the recovery of corals following disturbances, declined to 2%, over an order of magnitude lower compared to a year without elevated thermal stress, where 33% of coral recruits survived. While other research has shown that larger corals can bleach more frequently than smaller corals, we show the severe impact this phenomenon can have at the reef‐wide scale. As marine heatwaves become more frequent and intense, disproportionate mortality of the largest, most fecund corals and near‐complete loss of entire cohorts of newly‐settled coral recruits will likely reduce the recovery capacity of these iconic ecosystems. Abstract : Working in Moorea, French Polynesia, we investigated size‐dependent patterns of coral bleaching and mortality following a severe marine heatwave in 2019. Mass coral bleaching killed up to 76% and 65% of the largest individuals of the two dominant coral genera, Pocillopora, and Acropora, respectively. Additionally, the survivorship of microscopic coral recruits, critical for recovery following disturbances, declined to 2%, over an order of magnitude lower compared to a year without elevated thermal stress. As marine heatwaves become more frequent and intense, disproportionate mortality of the largest, most fecund corals and near‐complete loss of entire cohorts of coral recruits will likely reduce the recovery capacity of these iconic ecosystems.